2000
DOI: 10.1006/nimg.2000.0603
|View full text |Cite
|
Sign up to set email alerts
|

Functional Differentiation in the Human Auditory and Language Areas Revealed by a Dichotic Listening Task

Abstract: The human auditory cortex plays a special role in speech recognition. It is therefore necessary to clarify the functional roles of individual auditory areas. We applied functional magnetic resonance imaging (fMRI) to examine cortical responses to speech sounds, which were presented under the dichotic and diotic (binaural) listening conditions. We found two different response patterns in multiple auditory areas and language-related areas. In the auditory cortex, the medial portion of the secondary auditory area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 56 publications
9
41
0
1
Order By: Relevance
“…This general attentional effect is consistent with numerous auditory ERP studies (Hillyard et al, 1973;Woldorff et al, 1993; as well as with prior imaging studies using various speech (Grady et al, 1997;Hashimoto et al, 2000;Hugdahl et al, 2000;Hugdahl et al, 2003;Jancke et al, 2001;Jancke et al, 1999;O'Leary et al, 1997;Pugh et al, 1996;Vingerhoets & Luppens, 2001) and nonspeech (Hall et al, 2000;Jancke et al, 2003) auditory stimuli. Contrasts emphasizing speech sound processing (Speech-Rotated) and lexical processing (Word-Pseudoword) showed not only main effects of these stimulus variables but also strong interactions between attention and stimulus type.…”
Section: Discussionsupporting
confidence: 89%
“…This general attentional effect is consistent with numerous auditory ERP studies (Hillyard et al, 1973;Woldorff et al, 1993; as well as with prior imaging studies using various speech (Grady et al, 1997;Hashimoto et al, 2000;Hugdahl et al, 2000;Hugdahl et al, 2003;Jancke et al, 2001;Jancke et al, 1999;O'Leary et al, 1997;Pugh et al, 1996;Vingerhoets & Luppens, 2001) and nonspeech (Hall et al, 2000;Jancke et al, 2003) auditory stimuli. Contrasts emphasizing speech sound processing (Speech-Rotated) and lexical processing (Word-Pseudoword) showed not only main effects of these stimulus variables but also strong interactions between attention and stimulus type.…”
Section: Discussionsupporting
confidence: 89%
“…Recent fMRI studies have shown that the bilateral STG is related to auditory attention and conscious awareness of auditory stimuli [Hashimoto et al, 2000;Pugh et al, 1996], which is consistent with the fact that feedback control is conscious processing. However, the absence of significant activation in SLOW-NOR- Fig.…”
Section: Discussionsupporting
confidence: 66%
“…The supratemporal plane is likely to comprise several distinct areas, as indicated by changes in cortical architecture (Galaburda and Sanides 1980), and area-like structures were identified with cytochrome oxidase and acetylcholinesterase histochemistry (Rivier and Clarke 1997). Recent connectivity (Tardif and Clarke 2001) and activation studies (Hashimoto et al 2000;Wessinger et al 2001) suggest hierarchical organization of these areas within the ventral, recognition pathway. Furthermore, human primary auditory cortex was shown to contain distinct intra-areal compartments, cytochrome oxidase dark and light stripes, that are reminiscent of compartments within human V1 and V2 and that may represent an early segregation of different processing pathways (Clarke and Rivier 1998).…”
Section: Discussionmentioning
confidence: 99%